2008
DOI: 10.1097/mot.0b013e3283028312
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies, isotypes and complement in allograft rejection

Abstract: Considering the pivotal role of complement, technologies that uncover the complement-fixing ability of alloantibodies may be of particular interest for the selective detection of deleterious sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…This differentiation between clinically relevant and irrelevant DSAs is a major challenge, both before and after kidney [24,27,28]. For example, the pathogenetic roles of different Ig subclasses or those of complement-and non-complement-fixing DSAs in antibody-mediated rejection are controversially discussed [29]. On the one hand, complement-fixation is considered to be a major criterion for the pathogenicity of HLA antibodies in antibody-mediated rejection and has recently been confirmed in a large study with more than 1,000 patients [30].…”
Section: Detection Of Hla Antibodiesmentioning
confidence: 99%
“…This differentiation between clinically relevant and irrelevant DSAs is a major challenge, both before and after kidney [24,27,28]. For example, the pathogenetic roles of different Ig subclasses or those of complement-and non-complement-fixing DSAs in antibody-mediated rejection are controversially discussed [29]. On the one hand, complement-fixation is considered to be a major criterion for the pathogenicity of HLA antibodies in antibody-mediated rejection and has recently been confirmed in a large study with more than 1,000 patients [30].…”
Section: Detection Of Hla Antibodiesmentioning
confidence: 99%
“…Because the deleterious effects of DSAs, which are directed against HLA-A, -B, -DRB1, and DQB1 molecules, on kidney transplant outcomes have been well documented (Abe et al, 1997;Adeyi et al, 2005;Baid-Agrawal & Frei, 2007;Billen et al, 2009aBillen et al, , 2009bBohmig et al, 2008;Cai et al, 2006aCai et al, , 2006bChristiaans et al, 1998;Dunn et al, 2010;Gebel et al, 2009;Ghasemian et al, 1998;Kerman et al, 1997;Lederer et al, 1996;Lefaucheur et al, 2009;McKenna et al, 2000;Schonemann et al, 1998;Scornik et al, 1992;Terasaki, 2003;, this section of the review is focused on the role of antibodies against additional HLAs, such as C, non-DRB1 (DRB3, DRB4, and DRB5), DQA1, DPB1, and DPA1. This group of molecules are classical MHC antigens, meaning that, by definition, they are able to elicit cellular and humoral immune responses and present non-self antigens to CD8 (cytotoxic T lymphocytes) and CD4 (helper) T cells.…”
Section: Alloantibodies Against Hla Specificities and Their Impact Onmentioning
confidence: 99%
“…Subsequent IgG subtype analysis revealed that more than 50% of these antibodies were of the IgG2/IgG4 isotype (Lobashevsky et al, 2010). It is generally accepted that low (CDC assay-negative) concentrations of DSAs of the IgG isotype are not a contraindication for transplantation, provided that pre-and post-transplantation desensitization (DS) (see below) and proper DSA monitoring are used (Bohmig et al, 2008;Bray, 1994;Christiaans et al, 1998Christiaans et al, , 2000Graff et al, 2009;Martin et al, 2003;Patel et al, 2007;Reinsmoen et al, 2008;Vaidya et al, 2001). TCs with low DSA concentrations are considered to be medium risk patients due to higher AMR frequencies over a long-term (>5 years) follow up period in comparison to negative-DSA recipients (Gebel et al, 2009;Jordan et al, 2004Jordan et al, , 2006Reinsmoen et al, 2008;Vo et al, 2008).…”
Section: The Significance Of Alloantibody Concentration Isotype and mentioning
confidence: 99%
See 2 more Smart Citations